INTERNALISASI NILAI-NILAI AKHLAKUL KARIMAH SISWA MELALUI KETELADANAN GURU DI MTSN 1 BOGOR - Muhamad Badruddin; Sapiudin Shidiq (Qiro'ah : Jurnal Pendidikan Agama Islam, 2022)
This study aims to describe the internalization of the moral values of students through the example of teachers at MTsN 1 Bogor. This study uses a descriptive qualitative methodology. There are two kinds of data sources used in this study, namely primary data and secondary data. Primary data sources were obtained from direct interviews, including with the Principal, Deputy Principal for Curriculum, Deputy Principal for Student Affairs, PAI (Aqidah Akhlak) teachers, and students as well as the results of observations. While the secondary data sources were obtained from the study of documents, manuscripts and archives related to the internalization of students' moral values through the example of teachers at MTsN 1 Bogor. The results of this study indicate that the internalization of students' moral values which are pursued through the example of teachers at MTsN 1 Bogor is running and developing very well. In fact, it is very supportive of the cultivation of students' moral values. The supporting factors for these moral values are the full support of leadership from good schools, facilities and infrastructure such as prayer rooms and school activity programs. However, there are also factors that hinder the internalization process, namely the presence of teachers who are less concerned with the implementation of the internalization of moral values, lack of full support from students' parents. The implication or impact of internalizing the values of akhlakul karimah on students is to have a positive impact, namely students tend to be easily directed and formed; more active in learning because they have good learning motivation; students will be more accomplished; school activities become conducive and the school environment becomes comfortable and beautiful